Find expert answers and community support for all your questions on IDNLearn.com. Discover prompt and accurate responses from our experts, ensuring you get the information you need quickly.

Simplify the expression-6 -7 (c+10)A. 64 - 7 c B. -76 -7c C. 4 - 13 c D. -16 - 13c

Sagot :

Given:

[tex]-6-7(c+10)[/tex]

Simplify the expression,

[tex]\begin{gathered} -6-7(c+10) \\ \text{Expand : }-7(c+10)=-7c-70 \\ -6-7(c+10)=-6-7c-70 \\ -6-7(c+10)=-76-7c \end{gathered}[/tex]

Answer: Option B)

[tex]-6-7(c+10)=-76-7c[/tex]